Enhancing dough-making rheological performance of wheat flour by transglutaminase and vital gluten supplementation. (May 2018) - Bardini, Gloria; Boukid, Fatma; Carini, Eleonora; Curti, Elena; Pizzigalli, Emanuele; Vittadini, Elena
Abstract: The aim of this study was to optimize dough formulation using flours of different strength, through the supplementation of different levels of transglutaminase (TG) and vital gluten (VG). For this purpose, the experimental design took into consideration different factors including 3 different flour strengths (weak, medium and strong), 4 levels of TG (0, 0.05, 0.1 and 0.2% of flour weight), two levels of VG (0 and 1% of flour weight) and 4 different resting times (45, 70, 90 and 135 min). The rheological behavior of the obtained doughs was assessed using the SMS/Kieffer Dough and Gluten Extensibility Rig fitted to a texture analyzer. Multivariate analysis showed that dough resistance (R) and extensibility (E) were significantly (p ≤ 0.05) affected by all the studied factors, particularly flour strength and resting time. Considering data analysis results, the combinations enabling an increase in R for each flour type were identified: for strong flour (RT = 45min, TG = 0.2%, VG = 1%), medium flour (RT = 45min, TG = 0.1%, VG>1%) and weak flour (RT = 45min, TG>0.2%, VG>1%). Overall, results indicated that even low supplementation of TG and VG changed dough rheological quality of the flours strongly, suggesting further work to assess their influence on bread-making quality. Highlights: Transglutaminase and vital gluten were added to wheat flours of different strengths. Transglutaminase and vital gluten effect on the dough rheological performance was evaluated. Multivariate statistic was performed to assess interactions of factors on dough performance. Optimized dough formulations were identified to be tested on bread-making quality.